2011
DOI: 10.1186/1471-2229-11-153
|View full text |Cite
|
Sign up to set email alerts
|

A 48 SNP set for grapevine cultivar identification

Abstract: BackgroundRapid and consistent genotyping is an important requirement for cultivar identification in many crop species. Among them grapevine cultivars have been the subject of multiple studies given the large number of synonyms and homonyms generated during many centuries of vegetative multiplication and exchange. Simple sequence repeat (SSR) markers have been preferred until now because of their high level of polymorphism, their codominant nature and their high profile repeatability. However, the rapid applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
117
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 39 publications
13
117
2
1
Order By: Relevance
“…This system is plex-based and each plex contains 48 markers. Each variety was genotyped using seven plexes (336 SNPs minus four, which were repeated: 332 SNPs), as described in Cabezas et al (2011). Twenty nuclear microsatellites and four chloroplast microsatellites were also analyzed in some samples through the use of multiplex PCR and run in an Applied Biosystems 310 Genetic Analyzer ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This system is plex-based and each plex contains 48 markers. Each variety was genotyped using seven plexes (336 SNPs minus four, which were repeated: 332 SNPs), as described in Cabezas et al (2011). Twenty nuclear microsatellites and four chloroplast microsatellites were also analyzed in some samples through the use of multiplex PCR and run in an Applied Biosystems 310 Genetic Analyzer ).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to conventional nuclear SSR, SNPs have several features appropriate for large-scale genetic studies: they are abundant in most genomes surveyed (Brumfield et al 2003) and they have relatively low costs and the data are very easily scored, allowing a more feasible exchange of data between laboratories. SNPs have been used recently in grapevine for individual identification, integration of genetic and physical maps, and paternity inference (Cabezas et al 2011, Lijavetzky et al 2007) and in the study of genetic structure and domestication history of grape (Myles et al 2011). The power of SNPs for parentage inference has been reported previously (Anderson and Garza 2006), but almost exclusively in animal studies.…”
mentioning
confidence: 99%
“…Microsatellite and SNP markers have become in the last years the markers of choice for genetic analyses in grapevine, including genetic mapping and QTL identification (Huang et al 2012;Doligez et al 2013;Battilana et al 2013;Barba et al 2014), linkage disequilibrium and association analyses (Emanuelli et al 2010;Barnaud et al 2010;Cardoso et al 2012;Vargas et al 2013), and varietal identification (Myles et al 2010;Cabezas et al 2011;Laucou et al 2011;Migliaro et al 2012). As in many other woody plant species, genetic mapping in grapevine has been carried out using mainly the double pseudo test-cross strategy (Grattapaglia et al 1995), which is based on the study of allelic segregation of markers found in heterozygosis in one or both progenitors of an F 1 progeny.…”
Section: Applications Of the Developed Multiplex Pcrsmentioning
confidence: 99%
“…Moreover, wine quality control and falsification, respectively, can be analysed from DNA extracted from wine [28]. Other DNA markers such as AFLPs, M-AFLPs, SAMPLs, ISSRs, and SNPs [29] have also been suggested for studies of genetic variation accumulated over centuries of cultivation and selection in different environments.…”
Section: Discussionmentioning
confidence: 99%